IMPLEMENTASI KEBIJAKAN PROGRAM KARTU INDONESIA SEHAT DALAM PELAYANAN KESEHATAN MASYARAKAT DI KABUPATEN BUOL - Fahrul Rezza Ramadhan; Moch. Sakir; Rahmisyari Rahmisyari (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the implementation of the Kartu Indonesia Sehat (Healthy Indonesia Card / KIS) Program in public health services in Buol Regency, to identify its inhibiting factors, and to formulate efforts for its improvement. It employs George C. Edwards III’s policy implementation model, which covers communication, resources, disposition, and bureaucratic structure. A descriptive qualitative method was used, with data collected through in-depth interviews, observation, and documentation involving ten informants comprising policy organizers, primary and referral health facilities, the village government, and the community. The data were analyzed through data condensation, data display, and conclusion drawing, while validity was tested using source, technique, and theory triangulation. The results show that the KIS Program has been implemented but unevenly across aspects: communication is widespread yet not equitable, financial support is strong but human resources and facilities remain limited, the implementers’ disposition is strong, and the bureaucratic structure is well arranged but its administrative flow is lengthy. The four aspects are interdependent, so that a strong disposition is insufficient to offset resource and structural deficits; the dominant cross-cutting inhibiting factors are limited internet connectivity/digitalization and a shortage of health workers. The study recommends strengthening connectivity and offline communication, redistributing and incentivizing health workers, institutionalizing local adaptive mechanisms (Berani Sehat and REHAB), and simplifying administrative flows alongside proactive inter-agency coordination.